RHYTHM AND USUL AS PEDAGOGICAL AND PERFORMANCE PRINCIPLES IN MAQAM TRADITIONS - Ibragimov Abdinabi Begimqulovich (Western European Studies, 2025)
This article investigates the rhythmic foundation of Eastern maqam traditions through the concept of usul — a term encompassing both rhythmic pattern and structural organization in music. By tracing its historical development, theoretical interpretation, and practical application, the paper reveals how rhythm functions as both a pedagogical and performative principle in maqam-based musical culture. The study emphasizes the cognitive, mnemonic, and aesthetic aspects of rhythmic systems, showing their role in shaping the artistic dialogue between performer and listener.
Keywords: usual; rhythm; maqam; pedagogical principles